UNDERSTANDING NATURAL LANGUAGE PROCESSING (NLP) TECHNIQUES - V Khadake (INTERNATIONAL JOURNAL OF COMPUTER ENGINEERING AND TECHNOLOGY, 2024)
Artificial intelligence, linguistics, and cognitive psychology all come together in Natural Language Processing (NLP), an area that is changing quickly. This article discusses NLP's main methods, practical uses, and possible future developments. Key NLP techniques like sentiment analysis, language generation, and named object recognition are studied in depth and have various uses. NLP's Significant effects are discussed in many areas, such as virtual helpers, translation services, healthcare, finance, and education. NLP has come quite a way, but it still has issues with unclear words, understanding more than one language, and moral issues. More improvements will be made to model speed, interpretability, multimodal integration, and using common sense in the future. This review emphasizes NLP's transformative potential to change how people deal with computers and how information is processed in the digital age.